Implications od Perpres 12/2021 on MSEs Success in Public Procurement within Riau Province - Wide Enardi; Sri Maryati; Neng Kamarni (PT Mattawang Mediatama Solution, 2024)
Micro and small enterprises (MSEs) play a pivotal role in economic growth, particularly in government procurement. This study delves into the impact of policy changes, notably the implementation of Perpres 12 of 2021, on MSEs participating in procurement activities in Riau Province. Using a blend of quantitative and qualitative methodologies, this research explores the intricate relationship between various factors and the success of MSBs in procurement. Findings indicate that education, experience, workforce size, and capital significantly influence MSEs success in government procurement. Moreover, the policy implementation demonstrated substantial alterations in the correlation between independent variables and MSEs success. This article also provides strategic recommendations to bolster MSEs participation and success in government procurement, emphasizing policy adaptation, regulatory oversight, technological innovation, capacity-building programs, and stakeholder collaboration. Continuous policy evaluation and comprehensive data collection are advocated for future research endeavors to foster a deeper understanding of MSB success in procurement and its broader impact on regional economic growth.